2022
DOI: 10.1111/tan.14546
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the HLA system and weak antibody response to BNT162b2 mRNA vaccine

Abstract: The polymorphism of the HLA system has been extensively studied in COVID-19 infection, however there are no data about the role of HLA on vaccine response.We report here the HLA-A, -B, -C, and DRB1 allelic frequencies of n = 111 individuals after BNT162b2 mRNA vaccine, selected on the basis of lower antibody levels (<5% percentile) after the second dose among a total of n = 2569 vaccinees, and compare them with the frequencies of a reference population. We found that differences in the frequencies of the allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…This study found that HLA-A*03:01 frequency was decreased in weaker antibody responder after vaccination while frequencies of the alleles A*33:03, B* 58:01 were increased and thus associated with a weak humoral response. 50 The results of these last two studies are congruent with those from our study. Indeed, even in our cohort, A*03:01 is associated with a more efficient antibody response and DRB1*15:01 with a cellular response.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that HLA-A*03:01 frequency was decreased in weaker antibody responder after vaccination while frequencies of the alleles A*33:03, B* 58:01 were increased and thus associated with a weak humoral response. 50 The results of these last two studies are congruent with those from our study. Indeed, even in our cohort, A*03:01 is associated with a more efficient antibody response and DRB1*15:01 with a cellular response.…”
Section: Discussionsupporting
confidence: 90%
“…Common factors such as age, sex, pre-existing conditions, or immunosuppressive therapy have been investigated and shown to contribute to this variability ( Geisen et al, 2021 ; Lindemann et al, 2021 ; Simon et al, 2021 ; Steensels et al, 2021 ; Widge et al, 2021 ). In addition, genetic host factors are also likely to contribute to this variability ( Crocchiolo et al, 2022 ; Gutierrez-Bautista et al, 2022 ). However, to the best of our knowledge, no studies on vaccination against COVID-19 and G protein polymorphisms have been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies suggested that HLA polymorphisms might unlikely account for the wide disparities in COVID-19 prognosis, they concluded on the potential role of HLA polymorphisms on the development of SARS-CoV-2 immunity also after vaccination by evaluating the association between specific HLA variants and vaccine response ( Copley et al, 2021 ; Shukla et al, 2022 ). Even though a first extensive report excluded the HLA impact on the immunoglobulin level fluctuation and duration ( Ragone et al, 2021 ), particular attention has been later directed toward a selected locus ( HLA-A*03:01 ) associated to a weak antibody response and negative side effects after Pfizer–BioNTech vaccine ( Bolze et al, 2022 ; Crocchiolo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%